Implementation of the Personnel Management Information System (SIMPEG) at the Ministry of Religion of North Sumatra Province - Fathur Rahman; Andri Soemitra (Penerbit Jurnal Indonesia, 2022)
Describing the activities of adopting and implementing Information Communication and Technology (ICT) as a tangible manifestation of renewal in the government environment is the purpose of this research. This is also a form of evidence of changes and standardization of each employee, especially related to prime play. One of its manifestations is the North Sumatra Provincial Government's initiative to implement the Personnel Management Information System (SIMPEG) at the Ministry of Religion of North Sumatra Province. This study uses a descriptive qualitative approach by integrating primary and secondary data in order to analyze more deeply the implementation of SIMPEG. Therefore, as a recommendation is the need to increase the capacity of human resources through education and training including operational policies, budgets and network facilities.